Transmission Electron Microscopy of XDR Mycobacterium tuberculosis Isolates Grown on High Dose of Oﬂoxacin - Mohammad Arjomandzadegan; Maryam Sadrnia; Leonid Titov; Larissa Surkova; Hossein Sarmadian; Reza Ghasemikhah; Hossein Hosseiny (MDPI AG, 2017)
The aim of the study was to investigate behavior of resistant Mycobacterium tuberculosis (MTB) isolates under a high dose of oﬂoxacin and its morphological changes. 19 extensively drug resistant (XDR) clinical isolates of MTB were grown on Löwenstein-Jensen medium containing progressively increasing concentrations of oﬂoxacin (2, 4, 8, 16, 32 mg/L). Ultra-structure analyses of resistant isolates grown on oﬂoxacin were conducted by transmission electron microscopy (TEM). Fixation was carried out by 4% glutaraldehyde in 0.1 M sodium cacodylate buffer on 300 mesh carbon formvar copper grid. The samples were negatively stained with uranium acetate suspension. All19XDRMTBisolatesweregrownandformedcoloniessuccessfullyon2,4,8mg/L,sevenisolates on16mg/L,andfourisolateson32mg/Loﬂoxacin. Morphologicalchangesandunusualformswere detected in 8, 16 and 32 mg/L oﬂoxacin at 43%, 76.5% and 81% of cells, respectively. Swollen form (protoplast like), ghost-like cell, degraded forms, and in a few cases, detached cytoplasm from cell wall were clearly detected in high drug concentrations in comparison to control. Changes in morphology were increased with increasing oﬂoxacin concentrations (p < 0.05). Some XDR isolates could be successfully grown on high doses of oﬂoxacin (32 mg/L), but with changes in morphology. It was concluded that several magnitudes of the drug doses could not prevent growth of drug resistant forms.